DAMPAK ESKTERNALITAS AGROINDUSTRI TAHU TERHADAP MASYARAKAT DI KELUARAHAN GUNUNG SULAH KECAMATAN WAY HALIM KOTA BANDAR LAMPUNG: - Alysya Oktaviani; Fembriarti Erry Prasmatiwi; Erlina Rufaidah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study aimed to analyze the profitability of tofu agro-industry that excluded and included external costs, the willingness to pay (WTP) of the agro-industry for environmental costs, and the impact of externalities on the community in Gunung Sulah Sub-District, Way Halim District, Bandar Lampung City. This study used a case study method on six agro-industries and a survey of 70 community respondents. The analytical methods used were profit analysis, the contingency valuation method (CVM) to estimate the WTP value, and quantitative descriptive by analyzing social, economic, and environmental aspects to analyze externalities on the community. This study was conducted from April to May 2024. The study concluded that the average profit that excluded external cost was IDR10,249,656/month and IDR10,238,777/month including external costs. The average WTP value of the six agro-industries was IDR111,111/month, with a minimum of IDR45,833/month and a maximum of IDR220,833/month. Furthermore, the results of this study indicated that the largest positive externalities were from economic and social aspects, while the largest negative impacts were from environmental aspects. Key words: externalities, profits, tofu agroindustry, willingness to pay (WTP)